Definitive Endocrown Restoration in First Molar Right Mandibular After Multiple-Visit Endodontic Treatment: A Case Report - Christina Mahardika; Rizqika Sufi Aini; Luthfan Asyafiq; Muhamat Muhtar S Abdurrohman (Faculty of Dentistry, Universitas Islam Sultan Agung, 2026)
Background: Root canal treatment is a dental procedure aimed at preserving teeth and roots that have been infected by bacteria, with the expectation of restoring the tooth’s normal function and aesthetics. The selection of an appropriate final restoration plays a significant role in supporting the success of root canal therapy.Method: A 22-year-old male patient presented to the conservative dentistry clinic with a chief complaint of a cavity in the lower right molar that had been present for the past two years. The patient reported experiencing pain one year ago when the tooth was used for chewing or exposed to sweet and cold stimuli, accompanied by swelling, but no treatment was sought at that time. Currently, the patient no longer experiences pain but feels discomfort due to food impaction in the cavity. The ICD-10 diagnosis for tooth 46 was necrosis of the pulp.Result: The patient reported comfort during mastication and expressed satisfaction with the final restoration. These findings indicate the clinical success of the endocrown restoration, achieving optimal retention, occlusal function, and esthetic outcome.Conclusion: Endocrowns preserve more remaining tooth structure and provide good marginal adaptation. One week after placement, the evaluation showed satisfactory marginal adaptation with no post-treatment complaints. Therefore, endocrowns can be considered a conservative, functional, and esthetic restorative option for endodontically treated posterior teeth.